A global perspective on the pyrotechnologies of Sub-Saharan Africa. Issue 1 (2nd January 2016) - Killick, David
ABSTRACT: Although Sub-Saharan Africa has the oldest evidence for the deliberate production of fire, its recent record of pyrotechnology is more often presented as a list of absences than as a list of accomplishments. In this review I summarise the evidence, both before and after the initiation of long-distance trade with the Islamic world. The literature is decidedly unbalanced, with almost all attention so far having gone to African iron smelting, but the recent discovery of a unique type of glass production in Nigeria suggests that much more attention needs to be paid to other branches of pyrotechnology. I also suggest that we need to look outside the continent to understand why the record of preindustrial pyrotechnology in Sub-Saharan Africa is so different from that in other parts of the Old and New Worlds.